In vitro Activity of Apramycin Against Carbapenem-Resistant and Hypervirulent Klebsiella pneumoniae Isolates - Hao, Mingju; Shi, Xiaohong; Lv, Jingnan; Niu, Siqiang; Cheng, Shiqing; Du, Hong; Yu, Fangyou; Tang, Yi-Wei; Kreiswirth, Barry N.; Zhang, Haifang; Chen, Liang (Frontiers in Microbiology, 2020)
Objective: The emergence of carbapenem-resistant and hypervirulent Klebsiella pneumoniae (CR-hvKp) strains poses a significant public threat, and effective antimicrobial therapy is urgently needed. Recent studies indicated that apramycin is a potent antibiotic with good activity against a range of multi-drug resistant pathogens. In this study, we evaluated the in vitro activity of apramycin against clinical CR-hvKp along with carbapenem-resistant non-hvKp (CR-non-hvKp) isolates. Methods: Broth microdilution method was used to evaluate the in vitro activities of apramycin, gentamicin, amikacin, imipenem, meropenem, doripenem, ertapenem and other comparator “last-resort” antimicrobial agents, including ceftazidime-avibactam, colistin and tigecycline, against eighty-four CR-hvKp and forty CR-non-hvKp isolates collected from three Chinese hospitals. Multilocus Sequence typing (MLST), molecular capsule typing (wzi sequencing) and antimicrobial resistance genes were examined by PCR and Sanger sequencing. Pulsed-field gel electrophoresis and next generation sequencing were conducted on selected isolates. Results: Among the 84 CR-hvKp isolates, 97.6%, 100%, 97.6% and 100% were resistant to imipenem, meropenem, doripenem and ertapenem, respectively. Apramycin demonstrated an MIC50/MIC90 of 4/8 μg/mL against the CR-hvKp isolates. In contrast, the MIC50/MIC90 for amikacin and gentamicin were >64/>64 μg/mL. All CR-hvKp isolates were susceptible to ceftazidime-avibactam, colistin and tigecycline with the MIC50/MIC90 values of 0.5/1, 0.25/0.5, 1/1, respectively. For CR-non-hvKp, The MIC50/90 values for apramycin, gentamicin and amikacin were 2/8, >64/>64 and >64/>64 μg/mL, respectively. There were no statistical significance in the resistance rates of antimicrobial agents between CR-hvKp and CR-non-hvKp groups (p > 0.05). Genetic analysis revealed that all CR-hvKp isolates harbored blaKPC-2, and 94% (n=79) belong to the ST11 high-risk clone. 93.6% (44/47) of amikacin or gentamicin resistant strains carried 16S rRNA methyltransferases gene rmtB. Conclusion: Apramycin demonstrated potent in vitro activity against CR-hvKp isolates, including those were resistant to amikacin or gentamicin. Further studies are needed to evaluate the applicability of apramycin to be used as a therapeutic antibiotic against CR-hvKp infections.